Development of a High Precision Multi-channel Electric Control Pump Signal Monitoring System. (July 2020) - Bo, Wen; Yi, Jiangang; Xu, Ping
Abstract: The electric control hydraulic pump, which is the core of the hydraulic system, is widely used in modern industry. Therefore, it is necessary to monitor and control the signals of the electric control hydraulic pump in real time to improve the safety of the whole hydraulic system. In order to solve the safety and reliability problems of the operation of the electric control hydraulic pump equipment, a new high-precision multi-channel electric control pump signal monitoring system is proposed in this paper. The signal monitoring system of the electric control pump integrates high-precision power supply, multi-channel signal monitoring instrument and computer monitoring software as one automatic control and measuring device. The developed multi-channel signal monitor is powered by the power supply with good linearity and adjustable range voltage, and the monitor completes the data acquisition and data transmission task of the electric control pump system. The monitoring software on the remote computer processes and analyzes the real-time data of the equipment obtained from the network. The developed system improves the utilization ratio of electric hydraulic pump and has good application value.